Bioethanol production from microalgae polysaccharides - Lakatos, Gergely Ernő; Ranglová, Karolína; Manoel, João Câmara; Grivalský, Tomáš; Kopecký, Jiří; Masojídek, Jiří (Folia microbiologica, 2019)
The worldwide growing demand for energy permanently increases the pressure on industrial and scientific community to introduce new alternative biofuels on the global energy market. Besides the leading role of biodiesel and biogas, bioethanol receives more and more attention as first- and second-generation biofuel in the sustainable energy industry. Lately, microalgae (green algae and cyanobacteria) biomass has also remarkable potential as a feedstock for the third-generation biofuel production due to their high lipid and carbohydrate content. The third-generation bioethanol production technology can be divided into three major processing ways: (i) fermentation of pre-treated microalgae biomass, (ii) dark fermentation of reserved carbohydrates and (iii) direct "photo-fermentation" from carbon dioxide to bioethanol using light energy. All three technologies provide possible solutions, but from a practical point of view, traditional fermentation technology from microalgae biomass receives currently the most attention. This study mainly focusses on the latest advances in traditional fermentation processes including the steps of enhanced carbohydrate accumulation, biomass pre-treatment, starch and glycogen downstream processing and various fermentation approaches.
Keywords: mikrořasy; Biofuels; Biotechnology; biotechnologie; Fermentation; ethanol; biopaliva; fermentace; polysacharidy; Ethanol; Microalgae; Polysaccharides